The Ethics of buying and selling what premodern Christian Theologians have to say that's worth remembering - McCann, Dennis P. (2008)
When Christians search the Scriptures for answers to today's questions about the ethics of buying and selling, the results, at first, may not seem very promising. The New Testament's views of Christ instructing his disciples rarely yield lessons that today would be regarded as directly relevant to business ethics. To be sure, Jesus is remembered as saying, "It is easier for a camel to go through the eye of a needle, than for a rich man to enter into the Kingdom of God." (Matthew 19:24) But his point in saying so was not to single out the rich as uniquely sinful, but to emphasize that being saved or entering the Kingdom becomes possible only through God's power and grace. (Matthew 19:26) Nevertheless, there are many Biblical passages that may help to orient the construction of Christian business ethics. There are, for example, clear warnings against kings of cheating that too often occur in buying and selling, as in the Letter of James 5:1-6, which also repeats condemnations of the rich, already made memorable in the Old Testament (cf. Leviticus, Deuteronomy, Amos, etc.). But the rich are not condemned for being rich, but because of the ways too many of them have acquired their wealth, here epitomized in the all common practice of delaying the pavement of wages to hired workers, or cheating them out of them altogether, Compared to the teachings of the Old Testament, the New Testament offers no new guidance on the morality of the marketplace, save, possibly, the urgency with which the rich are challenged to change their ways before it is too late.
Keywords: Theologians; Christian ethics